2013
DOI: 10.1051/0004-6361/201322256
|View full text |Cite
|
Sign up to set email alerts
|

The spectral catalogue of INTEGRAL gamma-ray bursts

Abstract: We present the updated INTEGRAL catalogue of gamma-ray bursts (GRBs) observed between December 2002 and February 2012. The catalogue contains the spectral parameters for 59 GRBs localized by the INTEGRAL Burst Alert System (IBAS). We used the data from the two main instruments on board the INTEGRAL satellite: the spectrometer SPI (SPectrometer on INTEGRAL) nominally covering the energy range 20 keV−8 MeV, and the imager IBIS (the Imager on Board the INTEGRAL Satellite) operating in the range from 15 keV to 10 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 43 publications
2
51
1
Order By: Relevance
“…Although the number of correspondingly significant reported detections is relatively small (about ten detections a year for IBIS; Mereghetti 2012), the high INTEGRAL sensitivity in the hard X-ray domain efficiently probes a population of particularly faint and soft γ-ray bursts, with 20-200 keV fluences down to a few 10 −8 erg cm −2 (Bošnjak et al 2014). If at least a fraction of the LIGO/Virgo localization area for the future GW triggers overlap with the IBIS and/or SPI FoV, INTEGRAL observations could be used to localize and characterize in fairly good detail the corresponding electromagnetic counterparts, or at least put tight constraints on their hard X-ray/γ-ray emission (as is done in the present paper for LVT151012).…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of correspondingly significant reported detections is relatively small (about ten detections a year for IBIS; Mereghetti 2012), the high INTEGRAL sensitivity in the hard X-ray domain efficiently probes a population of particularly faint and soft γ-ray bursts, with 20-200 keV fluences down to a few 10 −8 erg cm −2 (Bošnjak et al 2014). If at least a fraction of the LIGO/Virgo localization area for the future GW triggers overlap with the IBIS and/or SPI FoV, INTEGRAL observations could be used to localize and characterize in fairly good detail the corresponding electromagnetic counterparts, or at least put tight constraints on their hard X-ray/γ-ray emission (as is done in the present paper for LVT151012).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this progress, still in the Fermi era it is found that the "Band" function provides reasonable fits to the vast majority of GRBs. [79][80][81][82][83][84] Many of these fits differ than earlier fits by the use of time-resolved analysis. Still, as explained above, in these fits "Band" model template was a-priori assumed, implying that "wiggles" could not be detected.…”
Section: Direct Evidencementioning
confidence: 99%
“…In addition, the complete table reported on line will make faster the searches for given GRBs. The following satellite missions and the associated catalogues have been taken into account: Agile by Galli, M. et al (2013);Pal'shin et al (2013); Longo, F. et al (2012); Hurley et al (2013), BeppoSAX by Frontera et al (2009), CGRO by Stern et al (2001); Kommers et al (2001);Schönfelder et al (2000) and the batsegrb catalogue Meegan et al 1996) in HEASARC web site 3 , Fermi with Paciesas et al (2012);von Kienlin et al (2014) and the fermigbrst catalogue in HEASARC archive 4 von Kienlin et al 2014;Goldstein et al 2012;Paciesas et al 2012), GRANAT, HETE-2, INTEGRAL by Minaev et al (2014); Bošnjak,Ž. et al (2014); Mereghetti (2013), Konus/Wind by Pal'shin et al (2013), Swift by Sakamoto et al (2011) and the "Swift GRB Table and Lookup" 5 ; ULYSSES by Hurley et al (1999).…”
Section: The Sample Selectionmentioning
confidence: 99%
“…In fact, we have matched various catalogues (i.e., Minaev et al (2014), Bošnjak,Ž. et al (2014), Mereghetti (2013), Pal'shin et al (2013)), in order to identify single different objects with respective coordinates, and to have a reasonable list for each of these missions.…”
Section: The Sample Selectionmentioning
confidence: 99%